Dressings cut to shape alleviate facial tissue loads while using an oxygen mask - Peko Cohen, Lea (Int Wound J, 2019)
Non‐invasive ventilation (NIV) masks are commonly used for respiratory support where intubation or a surgical procedure can be avoided. However, prolonged use of NIV masks involves risk to facial tissues, which are subjected to sustained deformations caused by tightening of the mask and microclimate conditions. The risk of developing such medical device‐related pressure ulcers can be reduced by providing additional cushioning at the mask‐face interface. In this work, we determined differences in facial tissue stresses while using an NIV mask with versus without using dressing cuts (Mepilex Lite; Mölnlycke Health Care, Gothenburg, Sweden). First, we developed a force measurement system that was used to experimentally determine local forces applied to skin at the bridge of the nose, cheeks, and chin in a healthy sample group while using a NIV mask. We further demonstrated facial temperature distributions after use of the mask using infrared thermography. Next, using the finite element method, we delivered the measured compressive forces per site of the face in the model and compared maximal effective stresses in facial tissues with versus without the dressing cuts. The dressings have shown substantial biomechanical effectiveness in alleviating facial tissues deformations and stresses by providing localised cushioning to the tissues at risk.